Internalisation or externalisation: the option for small and medium-sized technology-based enterprises in overseas markets. (1st January 2003) - Li, Lee; Qian, Gongming
Small and medium-sized firms interested in entering international markets face a difficult decision with regard to the choice of governance modes. The options available to a firm include internalisation and externalisation. Existing theories contradict each other about the strategic benefits of these options. This study compares these theories in the context of small and medium-sized technology-based enterprises. Findings from this study suggest that the merits of internalisation and externalisation vary with market contexts and the resources under the firm's control. Under certain conditions, one theory can be more powerful than the other.